Tax Advice and Reporting under Uncertainty: Theory and Experimental Evidence* - BECK, PAUL J.; DAVIS, JON S.; JUNG, WOON‐OH (Contemporary Accounting Research, 1996)
Abstract. This study extends the Beck, Davis, and Jung (1992) experimental study by incorporating opportunities for taxpayer subjects to purchase advice before making their tax reporting decisions. Tax advice has two roles in the model and experiment. First, tax advice allows taxpayers to reduce their uncertainty about the amount of taxes owed. This permits us to study the demand for tax advice in conjunction with its effect on tax reporting decisions. Second, the decision to purchase tax advice from an expert provides a means of signaling that may alter tax agency audit policies. The resulting audit policies, in turn, can affect taxpayers' decisions to purchase tax advice. These interdependencies are incorporated in a game‐theoretic model and several predictions are tested experimentally. Consistent with theory, subjects sorted themselves into three groups based upon their private information. Another prediction supported by the experiment is that the demand for tax advice increased with the magnitude of an uncertain tax deduction (amount‐at‐risk). We also found, as expected, that the effects of tax advice on pre‐audit tax revenues depend upon the amount‐at‐risk. When the amount‐at‐risk was high, subjects in settings with tax advice reported lower average incomes and paid lower taxes than did those subjects in settings without the opportunity to purchase tax advice. The opposite was true for the low amount‐at‐risk condition, supporting our prediction that tax advice and amount‐at‐risk would have an interactive effect on tax reporting. Analysis was also performed on post‐audit tax collections. Contrary to theory, post‐audit tax payments were found to increase when subjects had an opportunity to purchase tax advice. This result apparently was caused by a tendency to over‐purchase tax advice and, in some cases, to report a low income regardless of the advice received. Résumé. Les auteurs développent l'étude expérimentale de Beck, Davis et Jung (1992) en y incorporant la possibilité pour les sujets contribuables de solliciter des conseils avant de prendre leurs décisions relatives à l'information qu'ils fourniront aux fins fiscales. Les conseils fiscaux jouent deux rôles dans le modèle et l'expérience. Premièrement, ils permettent aux contribuables de réduire leur incertitude relative au montant des impôts auxquels ils sont assujettis. Les auteurs peuvent ainsi étudier la demande de conseils fiscaux en conjonction avec leurs conséquences sur les décisions relatives à l'information à fournir aux fins fiscales. Deuxièmement, la décision de solliciter les conseils fiscaux d'un expert est un signal pouvant influer sur les politiques de vérification des représentants du fisc. À leur tour, ces politiques peuvent influer sur les décisions des contribuables de solliciter des conseils fiscaux. Ces interdépendances ont été intégrées à un modèle de jeu théorique et les auteurs ont vérifié plusieurs prédictions par expérimentation. Conformément à la théorie, les sujets se sont répartis en trois groupes, en fonction de l'information privilégiée dont ils disposaient. L'expérimentation a confirmé une autre prédiction: la demande de conseils fiscaux augmente avec l'importance de la somme dont la déductibilité est incertaine (montant à risque). Les auteurs constatent également, comme ils s'y attendaient, que les effets des conseils fiscaux sur les recettes fiscales antérieures à la vérification dépendent du montant à risque. Lorsque le montant à risque est élevé, les sujets pouvant solliciter des conseils fiscaux font état de revenus moyens inférieurs et paient moins d'impôt que les sujets n'ayant pas la possibilité de solliciter des conseils fiscaux. L'inverse est vrai lorsque le montant à risque est faible, ce qui confirme la prédiction selon laquelle les conseils fiscaux et le montant à risque ont un effet interactif sur l'information fournie aux fins fiscales. Les auteurs analysent également les impôts perçus postérieurement à la vérification. Contrairement à la théorie, ils constatent que les paiements fiscaux postérieurs à la vérification augmentent lorsque les sujets ont eu la possibilité de solliciter des conseils fiscaux. Ce résultat semble être attribuable à une tendance à solliciter des conseils fiscaux avec excès et, dans certains cas, à faire état d'un faible revenu, malgré les conseils reçus.